A new score for airway assessment using clinical and ultrasound parameters - De Luis-Cabezón, Nekari; Ly-Liu, Diana; Renedo-Corcostegui, Pablo; Santaolalla-Montoya, Francisco; Zabala-Lopez de Maturana, Aitor; Herrero-Herrero, Jose Carlos; Martínez-Hurtado, Eugenio; De Frutos-Parra, Raúl; Bilbao-Gonzalez, Amaia; Fernandez-Vaquero, Miguel Angel (Frontiers in Medicine, 2024)
Background Over the last few years, ultrasonography has been introduced as the fifth pillar to patient’s bedside physical examination. Clinical assessments aim to screen and look for airway difficulties to predict difficult intubations, but none have demonstrated a significant predictive capacity. Recent systematic reviews have established a correlation between ultrasound imaging and difficult direct laryngoscopy. The primary objective of this study was to determine whether the utilization of ultrasonography to examine the upper airway could accurately predict difficult direct laryngoscopy. Methods This is a prospective observational study including 102 adult patients that required general anesthesia for elective surgery. Preoperatively, clinical airway assessments were performed. Data such as Mallampati-Samsoon grade (MS), upper lip bite test (ULBT), thyromental (TMD) and sternomental distance (SMD), cervical circumference (CC) and the Arné risk index were collected. Ultrasound evaluation was taken at five different levels in two planes, parasagittal and transverse. Therefore, the following measurements were registered: distance from skin to hyoid bone (DSHB), distance from skin to thyrohyoid membrane (DSTHM), distance from skin to epiglottis (DSE), distance from skin to thyroid cartilage (DSTC) and distance from hyoid bone and thyroid cartilage (DHBTC). Patients were divided into two groups based on the difficulty to perform direct laryngoscopy, according to Cormack-Lehane (C-L) classification. Grades I and II were classified as easy laryngoscopy and grades III or IV as difficult. Logistic regression models and the Receiver Operating Characteristic (ROC) curve was employed to determine the diagnostic precision of ultrasound measurements to distinguish difficult laryngoscopy (DL). Results The following risk score for DL was obtained, DSTHM ≥ 1.60 cm (2 points), DSTC ≥ 0.78 cm (3 points) and gender (2 points for males). The score can range from 0 to 7 points, and showed and AUC (95% CI) of 0.84 (0.74–0.95). A score of 5 points or higher indicates a 34-fold increase in the risk of finding DL (p = 0.0010), sensitivity of 91.67, specificity of 75.56, positive predictive value of 33.33, and negative predictive value of 98.55. Conclusion The use of ultrasonography combined with classic clinical screening tests are useful tools to predict difficult direct laryngoscopy.